Electrocatalysts with reduced noble metals aimed for hydrogen/oxygen evolution supported on Magneli phases. Part I: Physical characterization - P. Paunović, O. Popovski, G. Načevski, E. Lefterova, A. Grozdanov and A. T. Dimitrov (Bulgarian Academy of Sciences, Union of Chemists in Bulgaria, 2018)
The subject of this study is preparation and physical characterization of nano-scaled electrocatalysts for water electrolysis, consisted of Magneli phases as a support and different metallic phases (Co, Pt, Ru, CoPt (Co:Pt = 1:1 wt.), CoRu (Co:Ru = 1:1 wt.) and CoPtRu (Co:Pt:Ru = 1:0,5:0,5 wt.)). Magneli phases were mechanically treated (top-down approach) to reduce their particles from micro to nano scale. Electrocatalytic materials were prepared by sol-gel procedure using organometallic precursors (Me-acetylacetonate) deposited on dispersed Magneli phases in wt. ratio 10% Me and 90% Magneli phases. Pure Magneli phases and the studied electrocatalysts were characterized by means of TEM, XRD and BET analysis. The obtained results have shown that the size of the micro-scaled Magneli phases after the applied mechanical treatment, were reduced to 180÷200 nm. Specific surface area of 4.2 m2g–1 was determined by BET analysis. After grafting of the metallic phase over the Magneli phase, good dispersion of the catalytic centers over the support surface was achieved, that is appropriate for catalytic purpose. Metallic particles are nano-scaled in the range of 2 to 15 nm, thus the BET surface area of the electrocatalysts is higher (4.3 to 11 m2g–1) related to the BET surface area of pure Magneli phases.